Impact of age and clinical factors on the feasibility of mobile digital monitoring in people at risk of suicide - Ismael Conejero; Ana María de Granda-Beltrán; Lucía Albarracín-García; Alejandro Porras-Segovia; María Luisa Barrigón; Jorge López-Castromán; Phillippe Courtet; Antonio Artés-Rodriguez; Enrique Baca-García (PLoS ONE, 2026)
Objective Assessing the risk of suicidal outcomes is challenging, particularly in older people. Smartphone-based digital phenotyping may help to monitor suicide risk through ecological momentary assessment (EMA) applications. In this real-world study, we investigated if age and other clinical factors were associated with participation in EMA at baseline, and with retention in EMA monitoring among patients at risk of suicide. Methods Participation in EMA was determined by quantifying the installation of the MEmind mobile application in individuals involved in the SmartCrisis 1.0 and 2.0 studies. The patients were followed-up over a 6-month period. Results N = 512 patients met inclusion criteria, of which 387 installed the MEmind application on their smartphone. While age as a continuous variable was not associated with using EMA at baseline, being aged older than 50 and being engaged in an intimate relationship were independently associated with longer participation in EMA (OR 2.070, 95%CI [1.054–4.066], and OR 2.103, 95%CI [1.076–4.110], respectively). In an exploratory survival analysis, we found that EMA retention increased with age (p < 0.001). Conclusion Feasibility of EMA seems warranted in older people at risk of suicide. Clinicians should be encouraged to offer EMA monitoring to older adults, as they commonly face limitations in their access to healthcare facilities.